PENGARUH JUMLAH KREDIT DAN LIKUIDITAS TERHADAP TINGKAT PROFITABILITAS: Studi Kasus Pada KSP Kembang Ende - Bay, Wilhelmina; Djou, Laurentius D G; Sayang, Sabulon (Program Studi Akuntansi Universitas Flores, 2021)
This study aimed to determine the effect of the amount of credit and liquidity on the level of profitability of the Kembang Ende Savings and Loans Cooperative. The population of this study is the overall financial statements, balance sheets, and statistical data in the Kembang Ende Savings and Loans Cooperative. Based on the purposive sampling method, this study used samples of financial statements, balance sheets, and statistical data in the Kembang Ende Savings and Loans Cooperative from 2016 to 2020. The results of this study (1) the number of credits affects profitability, this is evidenced by the value of t count variable number of credits > t table (5.737> 4.303) with a significance value of t count of 0.029 < 0.05. (2) liquidity does not affect profitability, this is evidenced by the t value of the liquidity variable < t table (3.389<4.303) with a significance value of 0.077>0.05. The influence of the number of credit variables on profitability is 93.6%, while the remaining 16.4% is influenced by other variables that are not included in this research model.